Who Am I? uma arquitetura para a coleta, modelagem e oferta de perfis de usuários para a computação ubíqua - Alencar, Tatiana Silva de (2014)
One of the core requirements of Ubiquitous Computing is to be user context aware for software solutions developed may be adapted to the different skills and capabilities of users, with regard to physical and cognitive characteristics and interaction preferences. However, the focus of research has been in adapting the systems to different devices. The adaptation to different users profiles still demands further investigation, especially on how to understand and model the physical and cognitive characteristics, and users preferences. It is possible to find several studies that present user profiles models in the literature. Some of these models include a large set of features related to the users. However, only a few works provide an indication of how the information about the user is captured and how the profile already mapped in the model is turned available for applications. Moreover, these models do not take into account the user's interaction needs and preferences, since they only focus on personal information, physiological state, demographics etc. Thus, this work aims to support the flexibility of ubiquitous systems, considering different user profiles, facilitating the collection and delivery of these profiles for ubiquitous computing. To achieve this goal we defined the "Who Am I?" architecture to meet the users diversity by considering their interaction needs and preferences as part of the adopted user profile model; enables the collection of user profiles by means of a collector; and allows communication between the collector and the ubiquitous systems of an interoperable manner. To evaluate the feasibility of this architecture and verify that it meets the diversity of users, a case study was conducted with two scenarios of use. In the first scenario, a bus stop system and the second, a simulation for a smart kitchen was developed. The evaluation of the two software solutions developed was performed with real users and included both technical and emotional aspects. The results indicate that the interaction with both solutions through "Who Am I?" architecture gave satisfaction and motivation in users, and that communication and the adaptation of ubiquitous systems are given appropriately.